PrPC as a Transducer of Physiological and Pathological Signals - Panes, Jessica D.; Saavedra, Paulina; Pineda, Benjamin; Escobar, Kathleen; Cuevas, Magdalena E.; Moraga-Cid, Gustavo; Fuentealba, Jorge; Rivas, Coralia I.; Rezaei, Human; Muñoz-Montesino, Carola (Frontiers in Molecular Neuroscience, 2021)
After the discovery of prion phenomenon, the physiological role of the cellular prion protein (PrPC) remained elusive. Within the last decades, molecular and cellular analysis have shed some light regarding PrPC interactions and functions in health and disease. PrPC, which is located mainly at the plasma membrane of neuronal cells, attached by a GPI anchor, can act as a receptor or transducer from external signaling. Althought the precise role of PrPC remains elusive, a variety of functions have been proposed for this protein, including neuronal viability and excitability. Its connection to the central nervous system (CNS) and to several misfolding associated diseases make PrPC and interesting pharmacological target, although many issues must be solved in order to clearly define its role. In a physiological context, several reports have proposed that PrPC modulates synaptic transmission, interacting with several proteins that includes ion pumps, channes and metabotropic receptors. PrPC has also been implicated in the pathophysiological cell signaling induced by -amyloid peptide that leads to synaptic disfunction in the context of Alzheimer’s disease (AD), as a mediator of A-induced cell toxicity. In this review we analyze the role of PrPC as a transducer of physiological and AD-related pathological signaling.